A Triple-Layer Membrane with Hybrid Evaporation and Radiation for Building Cooling - Mingran Mao; Chunzao Feng; Junxian Pei; Huidong Liu; Haifeng Jiang (Energies, 2023)
Passive cooling for thermal comfort improvement has received extensive attention for its low energy consumption. However, most of the existing passive cooling technologies require a complex system design and supporting equipment, since they cool the ambient air. Herein, we propose a hybrid evaporative and radiative cooling membrane with a hygroscopic hydrogel sandwiched by two layers of a porous polyethylene aerogel (PEA). The hydrogel implements evaporative cooling. Combining the high solar reflection of PEA and the high infrared emissivity of hydrogel, this hybrid membrane also possesses radiative cooling. In addition, the high infrared transmittance and low thermal conductivity of PEA allow direct heat transfer between the hydrogel and human body, instead of the ambient air. Through comparative experiments and theoretical calculations, it is indicated that the net cooling power delivered by the hybrid membrane to the human body is up to 78.45 W m−2, which is much higher than that of conventional radiative cooling materials. Outdoor demonstration shows that emission below the hybrid membrane can achieve an average sub-ambient temperature drop of 6 °C, with a maximum of 14 °C, showing great potential for passive building cooling and human personal cooling.